The effect of linguistic proximity on the occupational assimilation of immigrant men in Canada - Alícia Adserà; Ana Ferrer (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
This paper contributes to the analysis of the integration of immigrants in the Canadian labour market by focusing in two relatively new dimensions. We combine the large samples of the restricted version of the Canadian Census (1991-2006) with both a new measure of linguistic proximity of the immigrant's mother tongue to that of the destination country, and with information of the occupational skills embodied in the jobs immigrants hold. This allows us to assess the role that language plays in the labour market performance of immigrants and to better study their career progression relative to the native born. Weekly wage differences between immigrants and the native born are driven mostly by penalties associated with immigrants' lower returns to social skills, but not to analytical or manual skills. Interestingly, low linguistic proximity between origin and destination language imposes larger wage penalties to the university-educated, and significantly affects the status of the jobs they hold. The influence of linguistic proximity on the skill content of jobs immigrants hold over time also varies by the educational level of the migrant. We also show that immigrants settling in Quebec and whose mother tongue is close to French have similar or better labour market outcomes (relative to native-born residents in Quebec) than immigrants with close linguistic proximity to English settling outside Quebec (relative to native born residents in the rest of Canada). However, since wages in Quebec are lower than elsewhere, immigrants in Quebec earn less in absolute terms than those residing elsewhere.
Keywords: 330